Enhanced Recovery from Chronic Ischemic Injury by Bone Marrow Cells in a Rat Model of Ischemic Stroke. Issue 2 (February 2015) - Yoo, Jongman; Seo, Jin-Ju; Eom, Jang-Hyeon; Hwang, Dong-Youn
Even after decades of intensive studies, therapeutic options for patients with stroke are rather limited. Thrombolytic drugs effectively treat the very acute stage of stroke, and several neuroprotectants that are designed to treat secondary injury following stroke are being tested in clinical trials. However, these pharmacological approaches primarily focus on acute stroke recovery, and few options are available for treating chronic stroke patients. In recent years, stem cell-mediated regenerative approaches have emerged as promising therapeutic strategies for treating the chronic stage of stroke. In this study, we examined whether systemically administered bone marrow cells (BMCs) could have beneficial effects in a rat model of chronic ischemia. Our transplantation experiments using BMCs obtained from ischemic donor rats showed functional and structural recovery during the chronic stage of stroke. BMC-mediated neural proliferation was prominent in the brains of rats with chronic stroke, and most of the new cells eventually became neurons instead of astrocytes. BMC-mediated enhanced neural proliferation coincided with a significant reduction (~50%) in the number of activated microglia, which is consistent with previous reports of enhanced neural proliferation being linked to microglial inactivation. Strikingly, approximately 57% of the BMCs that infiltrated the chronic ischemic brain were CD25 + cells, suggesting that these cells may exert the beneficial effects associated with BMC transplantation. Based on the reported anti-inflammatory role of CD25 + regulatory T-cells in acute experimental stroke, we propose a working model delineating the positive effects of BMC transplantation during the chronic phase of stroke; infiltrating BMCs (mostly CD25 + cells) reduce activated microglia, which leads to enhanced neural proliferation and enhanced recovery from neuronal damage in this rat model of chronic stroke. This study provides valuable insights into the effect of BMC transplantation in the chronic ischemic brain, which may lead to the development of effective therapy for chronic stroke patients who currently lack satisfactory therapeutic options.